Consequences of Chronic Nasal Obstruction on the Laryngeal Mucosa and Voice Quality of 4- to 12-Year-Old Children - de Labio, Roberto Badra [UNESP]; Mendes Tavares, Elaine Lara [UNESP]; Alvarado, Rafael Ceranto [UNESP]; Garcia Martins, Regina Helen [UNESP] (Mosby-elsevier, 2012)
Introduction. Dysphonia affects 6% to 23% of children, and chronic nasal obstruction may participate in its pathophysiology.Objectives. To study the effects of chronic nasal obstruction on children's vocal quality.Subjects and Methods. Two study groups were formed: nasal obstruction group (NOG), consisting of 60 children aged 4-12 years with important symptoms of chronic nasal obstruction; and a control group (CG), similar in gender and age range, consisting of healthy students without nasal, vocal, or auditory symptoms. The parents answered a questionnaire containing questions concerning their children's vocal qualities. All the children were submitted to perceptual auditory analysis, acoustic vocal analysis, auditory acuity assessment (transient otoacoustic emissions and/or threshold tone audiometry), and videoendoscopic assessment (flexible laryngoscopy and rigid laryngoscopy).Results. The groups were similar in age and gender. Parents reported a dysphonia rate of 76.6% in NOG and a vocal abuse rate of 68.3%. Eight children from NOG (13.34%) showed mild conductive hypoacusia. Laryngeal lesions were detected in 35 children from NOG (58%): inflammatory processes (n = 19), mucosal thickening (n = 10), nodules (n = 5), and cyst (n = 1). In children from the NOG were observed higher scores for the Grade, Roughness, Breathiness, Aesthenia, Strain, Instability (GRBAS) perceptual scale (P < 0.05), lower maximum phonation time values, and higher values to the s/z ratio, insufficient nasal resonance.Conclusions. Relevant changes in perceptual auditory and acoustic vocal analyses and in the videolaryngoscopy were detected in children with nasal obstruction. These results showed the importance of the assessment of nasal obstruction in dysphonic children.
Keywords: Children; Dysphonia; Nasal obstruction; Voice analysis